METODE DAN METODOLOGI DALAM DUNIA PENDIDIKAN: ANALISIS KONSEPTUAL TERHADAP PENERAPAN PEMBELAJARAN EFEKTIF - Saputra, Dicky Wahyu; Hayadi, B. Herawan; Tresna, Popy Wulandari; Fitriani, Pina; Samsuri, Samsuri; Ma’arif, Tubagus Mahar (Jurnal Ilmiah Pendidikan dan Keislaman, 2026)
Methods and methodologies are two fundamental concepts in education that play a crucial role in determining the success of the learning process. Learning methods relate to the methods used by educators to deliver learning materials to students, while methodology is a scientific study that discusses the principles, approaches, and frameworks underlying the use of these methods. This study aims to analyze the concepts of methods and methodologies in education and explain their relationship in improving the effectiveness of the learning process. This study uses a qualitative approach with a literature study method. Data were obtained from various library sources such as educational books, scientific journals, and academic documents relevant to the research topic. Data analysis was carried out through the stages of data reduction, data presentation, and drawing conclusions. The results of the study indicate that the use of appropriate learning methods can increase student engagement in the learning process, strengthen conceptual understanding, and develop critical and creative thinking skills. In addition, educational methodology serves as a scientific foundation that helps educators choose learning methods that are appropriate to learning objectives, student characteristics, and learning environment conditions. Thus, a comprehensive understanding of educational methods and methodologies is crucial for teachers in designing effective, innovative, and learner-centered learning processes. This research provides a conceptual contribution to the development of more systematic learning practices based on educational theory.